The disparities in clinical trials addressing urologic conditions among lower-income countries - Choksi, Ankur U.; Hayden, Christopher S.; Rahman, Syed N.; Lokeshwar, Soum D.; Kim, Isaac Y. (Frontiers in Urology, 2023)
Genitourinary pathologies are increasingly common in low and lower-middle income countries (LMICs) however there is a disproportionate distribution of clinical trials in higher income countries as compared to LMICs. In order for evidence-based practice to be implemented in LMICs with regards to urologic conditions and malignancies, clinical trials need to be performed within LMICs such that the results can be analyzed based on the context of the local environment. We queried ClinicalTrials.gov and the ICTRP for active clinical trials that were related to ‘prostatic neoplasms’, ‘urinary bladder neoplasms’, ‘kidney neoplasms’, ‘urolithiasis’, ‘urinary tract infections’ and ‘lower urinary tract symptoms’. The national incidence and DALYs was obtained from the Global Burden of Disease 2019 to analyze for a correlation between the numbers of clinical trials performed in a country with the burden of disease. A total of 4,169 clinical trials were identified based on the search query terms. Ninety percent of the clinical trials are being conducted in 32 countries. A majority of clinical trials are being performed in HICs. The proportion of non-oncologic urologic clinical trials performed in LMICs is greater than the proportion of urologic oncology clinical trials performed in LMICs (p < 0.001). Linear regression models demonstrates a weak relationship between the global burden of disease and the number of clinical trials conducted in each country for the individual urologic conditions. A majority of urologic clinical trials are being conducted in high-income countries which does not coincide with the global burden of disease of urologic conditions.